Activity choices of internally displaced persons and returnees: Quantitative survey evidence from post-war northern Uganda - Carlos Bozzoli; Tilman Brück; Tony Muhumuza (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
We study the effect of living in an internally displaced people's (IDP) camp on economic activity choices in post war northern Uganda. As the decision to relocate from a camp is voluntary, camp residents may be different from returnees. We merge household data with micro-level conflict data to control for endogeneity (selection of households out from camps). We find a strong effect of camp residence on activity choices. Particularly, individuals in IDP camps are more inclined to cultivate and engage in trading, than those who returned. However they are less likely to make handicrafts and participate in any of the wide range of activities. The observation that individuals living in camps strive to ensure self-reliance underscores the need for livelihood interventions and other recovery programmes to target not only returnee households but also create opportunities for households still in displacement. This should be coupled with improvement of security around camps to foster increased economic activity. Results also point to the need to fast-track infrastructure development and stimulate local demand that allows returnees to self-sustain.
Keywords: J01; O12; 330; activity choice; camp residents; conflict; Internally Displaced Persons; northern Uganda; returnees; Flüchtlinge; Binnenwanderung; Camping und Jugendherberge; Marktveranstaltung; Handwerk; Rückwanderung; Uganda